Evaluation of the Feasibility of the Content of the Integrated Thematic Book with the Theme of Our Friend's Environment for SD/MI Class V Published by Erlangga with the 2013 Curriculum Criteria - Nurdianasari, Nindya; Hasanah, Siti Aminatul; Finali, Zetti; Hutama, Fajar Surya; Satrijono, Hari (Widyagogik, 2023)
Textbooks are one of the teaching materials compiled by a person or group of people who are experts in their fields as instructional tools. Textbooks are arranged based on the applicable curriculum because textbooks have a function as the main source of information for students. Therefore, textbooks need to be evaluated for feasibility before being used. The purpose of this study was to find out the content of character values and the feasibility of the contents of the Integrated Thematic book Lingkungan Sahabat Kita for SD/MI Class V published by Erlangga with the 2013 curriculum criteria. The data collection method used is the documentation method. The evaluation results show that the Erlangga's Thematic Integrated Theme Lingkungan Sahabat Kita for SD/MI Class V published by Erlangga contains 8 character values contained in KI-1 and KI-2. In addition, the feasibility of the contents of the textbook obtained a percentage of 88.54% which was included in the very feasible category for use.